Lithium battery diaphragm with porous alumina-based composite material coating and preparation method of lithium battery diaphragm
By using a modified porous alumina-based composite coating in the lithium battery separator, the problems of insufficient ionic conductivity and liquid-absorbing and liquid retention ability of the existing separator are solved, and higher heat resistance, wetting and ionic conductivity are achieved, and the overall performance and safety of the lithium battery are improved.
Patent Information
- Application Number
- CN202411821610.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The ionic conductivity and liquid retention capacity of existing lithium battery separators limit the performance of the battery, especially in terms of high energy density and fast charging.
Modified porous alumina is formed by immersing the porous alumina in an aqueous solution of lithium salt, stirring and sonicating under vacuum environment to form modified porous alumina. As a coating component, the modified porous alumina improves the ionic conductivity and liquid-absorbing and liquid-retaining ability of the diaphragm.
It significantly improves the heat resistance, wetting and ionic conductivity of the lithium battery separator, reduces the internal resistance of the battery, improves the power density, and enhances the safety performance of the battery, avoiding short circuits and thermal runaway.
Smart Images

Figure CN119674428A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium battery separator with a porous alumina-based composite material coating and a preparation method thereof. Background Art
[0002] As a core component in the battery structure, the lithium battery separator has a vital dual function: on the one hand, it ensures the physical isolation between the positive and negative electrodes, effectively preventing the occurrence of short circuits; on the other hand, it allows lithium ions to pass smoothly to achieve the battery's charge and discharge cycle. This characteristic makes the ionic conductivity and liquid absorption and retention capacity of the separator a key factor affecting the battery's internal resistance, charge and discharge speed, and even the overall energy density and power performance. In view of this, improving the ionic conductivity and liquid absorption and retention capacity of the separator is not only a strategic point to optimize the performance of lithium batteries, but also a research frontier full of challenges and opportunities in the field of materials science.
[0003] In order to meet the urgent needs of modern electronic devices for higher energy density and faster charging speed, it is particularly important to explore and implement effective strategies to enhance the ion transmission efficiency and liquid retention capacity of lithium battery separators. This requires researchers to conduct innovative research in material design and synthesis, microstructure regulation and surface modification technology, aiming to develop new separator materials with better comprehensive performance.
[0004] In short, conducting in-depth and meticulous scientific research and technological innovation around how to efficiently improve the ionic conductivity and liquid absorption and retention rate of lithium battery separators will be of immeasurable value in promoting the development of high-performance lithium batteries and meeting the high standards required by future energy storage systems. Summary of the invention
[0005] In view of the deficiencies of the prior art, an object of the present invention is to provide a lithium battery separator with a porous alumina-based composite material coating.
[0006] Another object of the present invention is to provide a method for preparing the lithium battery separator having the porous alumina-based composite material coating.
[0007] Another object of the present invention is to provide a slurry.
[0008] The purpose of the present invention is achieved through the following technical solutions.
[0009] A lithium battery separator with a porous alumina-based composite material coating comprises a base film and a coating on the base film, wherein the coating comprises modified porous alumina, and the modified porous alumina comprises porous alumina and lithium elements loaded on the porous alumina.
[0010] In the above technical solution, the particle size of the porous alumina is: D10 = 0.225 ~ 0.356 μm, D50 = 0.512 ~ 0.672 μm, D90 = 1.356 ~ 1.478 μm, and the specific surface area of the porous alumina is 15 ~ 20 m 2 / g, the pore size of porous alumina is 10-50nm.
[0011] In the above technical solution, the particle size of the modified porous alumina is: D10 = 0.236 ~ 0.406 μm, D50 = 0.552 ~ 0.772 μm, D90 = 1.479 ~ 1.641 μm, and the specific surface area of the modified porous alumina is 15 ~ 20 m 2 / g.
[0012] In the above technical scheme, the method for preparing modified porous alumina comprises: immersing the porous alumina in an aqueous solution of lithium salt, stirring and ultrasonicating for 4 to 6 hours under a vacuum environment, drying the porous alumina and the aqueous solution of lithium salt in which the porous alumina is immersed, grinding into powder, and calcining at 400 to 600° C. for 2 to 4 hours under an inert gas atmosphere to obtain modified porous alumina, wherein the ratio of the porous alumina to the lithium salt in the aqueous solution of the lithium salt is (20 to 50) by mass:
[0013] (50-80), the concentration of lithium salt in the aqueous solution of lithium salt is 10-20wt%.
[0014] In the method for preparing modified porous alumina, the lithium salt is at least one of lithium chloride, lithium perchlorate, lithium hexafluorophosphate and lithium tetrafluoroborate.
[0015] In the method for preparing modified porous alumina, the porous alumina is dried at 60-80° C. for 2-3 hours before being immersed in an aqueous solution of lithium salt.
[0016] In the method for preparing modified porous alumina, the porous alumina is immersed in an aqueous solution of lithium salt, and stirred and ultrasonicated simultaneously for 4 to 6 hours in a vacuum environment, wherein the vacuum degree of the vacuum environment is 0.02 to 0.04 KPA, the stirring rotation speed is 200 to 300 r / min, the revolution speed is 20 to 30 r / min, and the ultrasonic frequency of the ultrasound is 5 to 8 kHz.
[0017] The preparation method of the above-mentioned porous alumina-based composite material coating lithium battery separator comprises: coating the slurry on the base film, drying, obtaining a coating on the base film, and obtaining the porous alumina-based composite material coating lithium battery separator, wherein the slurry comprises: modified porous alumina and water.
[0018] In the above technical solution, the thickness of the coating is 2 to 3 μm.
[0019] In the above technical solution, the coating speed is 10 to 20 m / min.
[0020] A slurry comprises: modified porous alumina, water, an adhesive and a dispersant. The ratio of the modified porous alumina, the water, the adhesive and the dispersant is (15-20): (60-80): (5-8): (0.5-0.8) by weight.
[0021] In the above technical solution, the adhesive is an acrylate copolymer solution, and the concentration of the acrylate copolymer in the acrylate copolymer solution is 10 to 30 wt %.
[0022] In the above technical solution, the dispersant is ammonium polyacrylate.
[0023] The method for preparing the slurry comprises: mixing the modified porous alumina, water, an adhesive and a dispersant until they are uniform to obtain the slurry.
[0024] The method for preparing the above slurry specifically comprises the following steps:
[0025] Step 1, mixing a dispersant, water and modified porous alumina until uniform to obtain a first solution;
[0026] In step 1, a dispersant, water and modified porous alumina are mixed, and stirred at a rotation speed of 2000 to 3000 r / min and a revolution speed of 40 to 50 r / min for 20 to 30 minutes until the mixture is uniform, thereby obtaining a first solution.
[0027] Step 2, mixing the first solution and the adhesive until uniform to obtain a slurry, wherein the ratio of the modified porous alumina, the water, the adhesive and the dispersant is (15-20): (60-80): (5-8): (0.5-0.8) by mass.
[0028] In step 2, the first solution and the adhesive are mixed, and stirred and ultrasonicated for 30 to 40 minutes in a vacuum environment until they are uniform to obtain a slurry, wherein the vacuum degree of the vacuum environment is 0.06 to 0.08 KPA, the stirring rotation speed is 2000 to 3000 r / min, the revolution speed is 40 to 60 r / min, and the ultrasonic frequency of the ultrasound is 5 to 8 kHz.
[0029] The modified porous alumina is used to improve the heat resistance, liquid absorption rate, liquid retention rate, air permeability and / or ion conductivity of a diaphragm. The modified porous alumina comprises: porous alumina and lithium elements loaded on the porous alumina.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. High heat resistance: The lithium battery separator of the present invention has excellent high heat resistance. The lithium battery separator with high heat resistance is a key factor in improving the safety and cycle stability of lithium batteries. This high temperature resistance can effectively prevent battery short circuit or thermal runaway caused by excessive temperature, thereby significantly improving the safety performance of the battery.
[0032] 2. High wettability and high ion conductivity: The lithium battery separator of the present invention has excellent wettability and ion conductivity. The coating of the present invention contains porous aluminum oxide, so it has a rich pore structure, which greatly enhances the absorption and storage capacity of the separator for electrolyte. It not only shortens the Li + It not only shortens the transmission path, but also improves the ionic conductivity of the diaphragm, thereby reducing the internal resistance of the battery and improving the power density.
[0033] 3. High safety: Higher ionic conductivity can effectively slow down the accumulation of lithium and make lithium ions more evenly distributed in the negative electrode, thereby slowing down the growth of lithium dendrites and preventing short circuit and thermal runaway. The lithium battery separator of the present invention has a tortuous porous structure, which can block the penetration of lithium dendrites, improve the safety performance of the battery, and avoid the risk of overheating and combustion. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the SEM of the lithium battery separator prepared in Example 6. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0036] Porous alumina (powder): The particle size of porous alumina is: D10 = 0.306 μm, D50 = 0.595 μm, D90 = 1.388 μm, and the specific surface area of porous alumina is 16.6 m 2 / g, the pore size of porous alumina is 50nm;
[0037] Acrylate copolymer solution: Baoding Lucky Imaging Material Technology Co., Ltd.;
[0038] Ammonium polyacrylate: Shanghai Sanrui Polymer Materials Technology Co., Ltd.
[0039] Double planetary mixer: XFZH-30L.
[0040] In the following examples, water is pure water.
[0041] In the following embodiments, the base film is a PE film, and the thickness of the PE film is 7 microns.
[0042] Ionic conductivity: tested at 25°C and 60% relative humidity.
[0043] Example 1
[0044] A method for preparing a slurry comprises the following steps:
[0045] Step 1, mixing a dispersant, water and modified porous alumina in a double planetary mixer, stirring for 20 minutes at a rotation speed of 2000 r / min and a revolution speed of 40 r / min until uniform, to obtain a first solution, wherein the dispersant is ammonium polyacrylate;
[0046] Step 2, adding an adhesive to the first solution (the adhesive is an acrylate copolymer solution, the concentration of the acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide), stirring and ultrasonicating for 30 minutes in a double planetary mixer with ultrasonic oscillation function under a vacuum environment until uniform, to obtain a slurry, in which the ratio of modified porous alumina, water, adhesive and dispersant is 15:79.5:5:0.5 by mass, wherein the vacuum degree of the vacuum environment is 0.06KPA, the rotation speed of the stirring is 2000r / min, the revolution speed is 40r / min, and the ultrasonic frequency of the ultrasound is 5kHz.
[0047] The method for preparing modified porous alumina comprises: immersing the porous alumina in an aqueous solution of lithium salt (before immersing the porous alumina in the aqueous solution of lithium salt, drying it in an oven at 60°C for 2h), and stirring and ultrasonicating it in a double planetary mixer with ultrasonic oscillation function in a vacuum environment for 4h (the vacuum degree of the vacuum environment is 0.02KPA, the rotation speed of stirring is 200r / min, the revolution speed is 20r / min, and the ultrasonic frequency of the ultrasonic wave is 5kHz), drying the porous alumina and the aqueous solution of lithium salt in which it is immersed in an oven at 60°C for 2h, grinding it into powder, placing it in a tube furnace, and calcining it at 400°C for 2h in an argon atmosphere to obtain modified porous alumina (the particle size of the modified porous alumina is D10=0.267μm, D50=0.615μm, D90=1.512μm, and the average specific surface area of the modified porous alumina is 17.2m 2 / g), wherein the ratio of the porous alumina to the lithium salt in the aqueous solution of the lithium salt is 20:80 by mass, the concentration of the lithium salt in the aqueous solution of the lithium salt is 10wt%, and the lithium salt is lithium chloride.
[0048] Example 2
[0049] A method for preparing a slurry comprises the following steps:
[0050] Step 1, mixing a dispersant, water and modified porous alumina in a double planetary mixer, stirring for 25 minutes at a rotation speed of 2500 r / min and a revolution speed of 45 r / min until uniform, to obtain a first solution, wherein the dispersant is ammonium polyacrylate;
[0051] Step 2, adding an adhesive to the first solution (the adhesive is an acrylate copolymer solution, the concentration of the acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide), stirring and ultrasonicating for 35 minutes in a double planetary mixer with ultrasonic oscillation function under a vacuum environment until uniform, to obtain a slurry, in which the ratio of modified porous alumina, water, adhesive and dispersant is 17:75.3:7:0.7 by mass, wherein the vacuum degree of the vacuum environment is 0.07KPA, the rotation speed of the stirring is 2500r / min, the revolution speed is 50r / min, and the ultrasonic frequency of the ultrasound is 6kHz.
[0052] The method for preparing modified porous alumina comprises: immersing the porous alumina in an aqueous solution of lithium salt (before immersing the porous alumina in the aqueous solution of lithium salt, drying it in an oven at 70°C for 2.5 hours), and stirring and ultrasonicating it in a double planetary mixer with ultrasonic oscillation function in a vacuum environment for 5 hours (the vacuum degree of the vacuum environment is 0.03KPA, the rotation speed of stirring is 250r / min, the revolution speed is 30r / min, and the ultrasonic frequency of the ultrasonic wave is 5kHz), drying the porous alumina and the aqueous solution of lithium salt in which it is immersed in an oven at 70°C for 2.5 hours, grinding it into powder, placing it in a tube furnace, and calcining it at 500°C for 3 hours in an argon atmosphere to obtain modified porous alumina (the particle size of the modified porous alumina is D10=0.289μm, D50=0.587μm, D90=1.625μm, and the average specific surface area of the modified porous alumina is 18.6m 2 / g), wherein the ratio of the porous alumina to the lithium salt in the aqueous solution of the lithium salt is 30:70 by mass, the concentration of the lithium salt in the aqueous solution of the lithium salt is 15wt%, and the lithium salt is lithium chloride.
[0053] Example 3
[0054] A method for preparing a slurry comprises the following steps:
[0055] Step 1, mixing a dispersant, water and modified porous alumina in a double planetary mixer, stirring for 30 minutes at a rotation speed of 3000 r / min and a revolution speed of 50 r / min until uniform, to obtain a first solution, wherein the dispersant is ammonium polyacrylate;
[0056] Step 2, adding an adhesive to the first solution (the adhesive is an acrylate copolymer solution, the concentration of the acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide), stirring and ultrasonicating for 40 minutes in a double planetary mixer with ultrasonic oscillation function under a vacuum environment until uniform, to obtain a slurry, in which the ratio of modified porous alumina, water, adhesive and dispersant is 20:71.2:8:0.8 by mass, wherein the vacuum degree of the vacuum environment is 0.08KPA, the rotation speed of the stirring is 3000r / min, the revolution speed is 60r / min, and the ultrasonic frequency of the ultrasound is 8kHz.
[0057] The method for preparing modified porous alumina comprises: immersing the porous alumina in an aqueous solution of lithium salt (before immersing the porous alumina in the aqueous solution of lithium salt, drying it in an oven at 80°C for 3 hours), and stirring and ultrasonicating it in a double planetary mixer with ultrasonic oscillation function in a vacuum environment for 6 hours (the vacuum degree of the vacuum environment is 0.04KPA, the stirring rotation speed is 300r / min, the revolution speed is 20r / min, and the ultrasonic frequency of the ultrasonic wave is 5kHz), drying the porous alumina and the aqueous solution of lithium salt in which it is immersed in an oven at 80°C for 3 hours, grinding it into powder, placing it in a tube furnace, and calcining it at 600°C for 4 hours in an argon atmosphere to obtain modified porous alumina (the particle size of the modified porous alumina is D10=0.299μm, D50=0.633μm, D90=1.586μm, and the average specific surface area of the modified porous alumina is 20m 2 / g), wherein the ratio of the porous alumina to the lithium salt in the aqueous solution of the lithium salt is 50:50 by mass, the concentration of the lithium salt in the aqueous solution of the lithium salt is 20wt%, and the lithium salt is lithium chloride.
[0058] Example 4 (for comparison)
[0059] A method for preparing a slurry is basically the same as Example 1, except that the "by mass percentage, the ratio of the porous alumina to the lithium salt in the aqueous solution of the lithium salt is 20:80" in the method for preparing modified porous alumina is replaced by "by mass percentage, the ratio of the porous alumina to the lithium salt in the aqueous solution of the lithium salt is 10:90".
[0060] Example 5 (for comparison)
[0061] A method for preparing a slurry is basically the same as Example 1, except that the "by mass percentage, the ratio of the porous alumina to the lithium salt in the aqueous solution of the lithium salt is 20:80" in the method for preparing modified porous alumina is replaced by "by mass percentage, the ratio of the porous alumina to the lithium salt in the aqueous solution of the lithium salt is 60:40".
[0062] Comparative Example 1
[0063] A method for preparing a slurry comprises the following steps:
[0064] Step 1, mixing a dispersant, water and porous alumina (the same as the porous alumina used in Example 1) in a double planetary mixer, stirring at a rotation speed of 3000 r / min and a revolution speed of 45 r / min for 25 min until uniform, to obtain a solution A, wherein the dispersant is ammonium polyacrylate;
[0065] Step 2, adding an adhesive to solution A (the adhesive is an acrylate copolymer solution, the concentration of the acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide), stirring and ultrasonicating for 40 minutes in a double planetary mixer with ultrasonic oscillation function under a vacuum environment until uniform, to obtain a slurry, in which the ratio of porous alumina, water, adhesive and dispersant is 20:73.5:6:0.5 by mass, wherein the vacuum degree of the vacuum environment is 0.07KPA, the rotation speed of the stirring is 2500r / min, the revolution speed is 60r / min, and the ultrasonic frequency of the ultrasound is 6kHz.
[0066] Comparative Example 2
[0067] A method for preparing a slurry comprises the following steps:
[0068] Step 1, mixing a dispersant, water and alumina (D10=0.299 μm, D50=0.605 μm, D90=1.533 μm, non-porous alumina) in a double planetary mixer, first stirring at a rotation speed of 3000 r / min and a revolution speed of 50 r / min for 20 min, and then ultrasonicating at a frequency of 5 kHz for 20 min until uniform, to obtain a B solution, wherein the dispersant is ammonium polyacrylate;
[0069] Step 2, adding an adhesive to solution B (the adhesive is an acrylate copolymer solution, the concentration of the acrylate copolymer in the acrylate copolymer solution is 20wt%, and the acrylate copolymer is copolymerized by acrylic acid and acrylamide), stirring and ultrasonicating for 30 minutes in a double planetary mixer with ultrasonic oscillation function under a vacuum environment until uniform, to obtain a slurry, in which the ratio of alumina, water, adhesive and dispersant is 20:74.5:5:0.5 by mass, wherein the vacuum degree of the vacuum environment is 0.06KPA, the rotation speed of the stirring is 2000r / min, the revolution speed is 40r / min, and the ultrasonic frequency of the ultrasound is 5kHz.
[0070] Examples 6 to 10 and Comparative Examples 3 to 4
[0071] A method for preparing a lithium battery separator comprises: placing a base film on a coating machine containing a slurry, coating the slurry on one side of the base film at a coating speed of X m / min, pulling the base film into a drying device through a traction roller and drying it at Y°C for Z min, obtaining a coating on the base film, and obtaining a lithium battery separator. The slurry is one of Examples 1 to 5 and Comparative Examples 1 to 2.
[0072] X, Y and Z are shown in Table 1.
[0073] Table 1
[0074]
[0075] The parameters of the lithium battery separator prepared from the slurry of Example 1 are as follows:
[0076]
[0077]
[0078] The parameters of the lithium battery separator prepared from the slurry of Example 2 are as follows:
[0079]
[0080] The parameters of the lithium battery separator prepared from the slurry of Example 3 are as follows:
[0081]
[0082]
[0083] The parameters of the lithium battery separator prepared from the slurry of Example 4 are as follows:
[0084]
[0085] The parameters of the lithium battery separator prepared from the slurry of Example 5 are as follows:
[0086]
[0087] The parameters of the lithium battery separator prepared from the slurry of Comparative Example 1 are as follows:
[0088]
[0089] The parameters of the lithium battery separator prepared from the slurry of Comparative Example 2 are as follows:
[0090]
[0091] The pore structure test of the lithium battery separator prepared from the slurry of Example 1 was carried out, and the test results are as follows:
[0092]
[0093] Traditional lithium battery separators often have the problem of low ion transfer efficiency, which limits the overall performance of the battery. The present invention uses lithium salts to modify porous alumina. By introducing lithium salts with high ion conductivity on the surface and pore walls of porous alumina, this strategy significantly improves the ion conductivity of lithium battery separators. Specifically, the large specific surface area of porous alumina is used as a supporting platform, and the lithium salt is evenly dispersed on the surface and pore structure of porous alumina using a solution impregnation method. The unique structure of porous alumina provides more active sites for lithium salts, which promotes the rapid transmission of lithium ions in the separator. In addition, the introduction of lithium salts also enhances the compatibility between the separator and the electrolyte, further improving the ionic conductivity.
[0094] The test results of the examples and comparative examples show that the lithium battery separator prepared by modified porous alumina exhibits excellent ionic conductivity and liquid absorption and retention rate while maintaining good thermal shrinkage. This provides new ideas and methods for the development of high-performance lithium battery separator materials, and is expected to promote the progress and development of lithium battery technology.
[0095] Figure 1 This is the SEM of the lithium battery separator prepared in Example 6.
[0096] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A lithium battery separator with a porous alumina-based composite material coating, characterized in that: include: The base film and the coating on the base film, the coating comprises: modified porous alumina, and the modified porous alumina comprises: porous alumina and lithium element loaded on the porous alumina.
2. The lithium battery separator of the porous alumina-based composite material coating according to claim 1, characterized in that: The particle size of the porous alumina is: D10=0.225-0.356 μm, D50=0.512-0.672 μm, D90=1.356-1.478 μm, and the specific surface area of the porous alumina is 15-20 m 2 / g, the pore size of porous alumina is 10-50nm.
3. The lithium battery separator of the porous alumina-based composite material coating according to claim 1, characterized in that: The particle size of the modified porous alumina is: D10=0.236-0.406 μm, D50=0.552-0.772 μm, D90=1.479-1.641 μm, and the specific surface area of the modified porous alumina is 15-20 m 2 / g.
4. The lithium battery separator of the porous alumina-based composite material coating according to claim 1, characterized in that: The method for preparing modified porous alumina comprises: immersing the porous alumina in an aqueous solution of a lithium salt, stirring and ultrasonicating the porous alumina for 4 to 6 hours under a vacuum environment, drying, grinding the porous alumina into powder, and calcining the powder at 400 to 600° C. under an inert gas atmosphere for 2 to 4 hours to obtain the modified porous alumina, wherein the ratio of the porous alumina to the lithium salt in the aqueous solution of the lithium salt is (20 to 50): (50 to 80) by mass, and the concentration of the lithium salt in the aqueous solution of the lithium salt is 10 to 20 wt%.
5. The method for preparing a lithium battery separator having a porous alumina-based composite material coating according to any one of claims 1 to 4, characterized in that: include: The slurry is coated on a base film and dried to obtain a coating on the base film, thereby obtaining a lithium battery separator with a porous alumina-based composite material coating. The slurry includes: modified porous alumina and water.
6. A slurry, characterized in that: include: The modified porous alumina, water, adhesive and dispersant are in the ratio of (15-20): (60-80): (5-8): (0.5-0.8) by weight.
7. The method for preparing the slurry according to claim 6, characterized in that: include: The modified porous alumina, water, an adhesive and a dispersant are mixed until uniform to obtain a slurry.
8. Application of modified porous alumina in improving the heat resistance of a diaphragm, the modified porous alumina comprising: Porous alumina and lithium element supported on the porous alumina.
9. Application of modified porous alumina in improving liquid absorption rate and liquid retention rate of diaphragm, the modified porous alumina comprising: Porous alumina and lithium element supported on the porous alumina.
10. Application of modified porous alumina in improving ion conductivity or air permeability of a diaphragm, the modified porous alumina comprising: Porous alumina and lithium element supported on the porous alumina.
Citation Information
Patent Citations
Polyoxometallic acid lithium ceramic diaphragm of lithium ion battery
CN104051693A
Ceramic coating diaphragm for lithium battery and preparation method of ceramic coating diaphragm
CN104269509A
Dendrite inhibiting electrolytes for metal-based batteries
CN106463711A
Method for preparing porous alumina composite ceramic powder
CN109665822A
Porous alumina powder for lithium ion battery, battery diaphragm, battery and electric equipment
CN119038966A